Single-crystal-to-single-crystal post-synthetic modifications of three-dimensional LOFs (Ln = Gd, Eu): a way to modulate their luminescence and thermometric properties. Issue 18 (22nd April 2020) - De Bellis, Jacopo; Bellucci, Luca; Bottaro, Gregorio; Labella, Luca; Marchetti, Fabio; Samaritani, Simona; Belli Dell'Amico, Daniela; Armelao, Lidia
Abstract : Single-crystal-to-single-crystal post-synthetic modifications of [Ln2 (H2 L)3 (DMF)4 ]·2DMF n LOFs (Ln = Gd, Eu) to modulate their luminescence and thermometric properties. Abstract : Single-crystal-to-single-crystal post-synthetic modifications (PSMs) of Lanthanide Organic Frameworks (LOFs) [Ln2 (H2 L)3 (DMF)4 ]·2DMF n (Ln = Gd, 1 and Eu, 2 ; H4 L = 2, 5-dihydroxyterephthalic acid; DMF = dimethylformamide), carried out by treatment with (a) chloroform or (b) an imidazole solution in chloroform, yielded respectively isostructural [Ln2 (H2 L)3 (DMF)4 ]·CHCl3 n (Ln = Gd, 3 ; Eu, 4 ) or [Ln2 (H2 L)3 (Im)4 ][Ln2 (H2 L)3 (Im)2 (H2 O)2 ]·6Im·2CHCl3 n (Ln = Gd, 5 ; Eu, 6 ). Single crystal X-ray diffraction studies of 5 showed two different regularly alternating dimeric units in the LOF and two regularly alternating cavities with different guest molecules. All compounds revert to the parent LOF, 1 or 2, when treated with DMF at 90 °C for 8 h. Europium-LOFs (2, 4 and 6 ) showed a faint red emission that progressively gained intensity upon cooling from RT to liquid nitrogen temperature. This behaviour was exploited to develop a family of luminescent thermometers whose characteristics were affected by the structural and coordinative modifications induced by PSMs.